PENGARUH KOMPETENSI, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Survei pada Pegawai BPS Kabupaten Sragen) - Nia Fatmawati; Rahayu Triastity; Erni Widajanti (Universitas Slamet Riyadi, 2021)
This research uses qualitative and quantitative data. Sources of data used are secondary and primary data.Sources of data used are secondary and primary data.The population in this study amounted to 37 employees, because the population was below 100, the sampling technique was total sampling, that is, all members were used as the sample (census).The data analysis technique used descriptive analysis, multiple linear regression, t test, F test, and the coefficient of determination.The results of this study indicate that partially or simultaneously competence, work motivation, work environment have a significant effect on employee performance.